Matrix factorizations and mirror symmetry: the cubic curve - Brunner, Ilka; Walcher, Johannes (Journal of high energy physics, 2006)
We revisit open string mirror symmetry for the elliptic curve, using matrix factorizations for describing D -branes on the B -model side. We show how flat coordinates can be intrinsically defined in the Landau-Ginzburg model, and derive the A -model partition function counting disk instantons that stretch between three D -branes. In mathematical terms, this amounts to computing the simplest Fukaya product m 2 from the LG mirror theory. In physics terms, this gives a systematic method for determining non-perturbative Yukawa couplings for intersecting brane configurations.